Effects of Acute Intravenous Administration of Pentamidine, a Typical hERG-Trafficking Inhibitor, on the Cardiac Repolarization Process of Halothane-Anesthetized Dogs - Hirofumi Yokoyama; Yuji Nakamura; Hiroshi Iwasaki; Yukitoshi Nagayama; Kiyotaka Hoshiai; Yoshitaka Mitsumori; Atsushi Sugiyama (Elsevier, 2009)
Abstract.: Although acute treatment of pentamidine does not directly modify any ionic channel function in the heart at clinically relevant concentrations, its continuous exposure can prolong QT interval. Recent in vitro studies have indicated that hERG trafficking inhibition may play an important role in the onset of pentamidine-induced long QT syndrome. In this study, we examined acute in vivo electropharmacological effects of pentamidine using the halothane-anesthetized canine model (n = 5). The clinically relevant total dose of 4 mg/kg of pentamidine (namely, 1 mg/kg, i.v. over 10 min followed by 3 mg/kg, i.v. over 10 min with a pause of 20 min) decreased the mean blood pressure, ventricular contraction, preload to the left ventricle, and peripheral vascular resistance. Pentamidine also enhanced the atrioventricular conduction in parallel with its cardiohemodynamic actions, but it gradually prolonged both the ventricular repolarization period and effective refractory period, whereas no significant change was detected in the intraventricular conduction. Thus, acute administration of a clinically relevant dose of pentamidine can suppress cardiac function and vascular tone with reflex-mediated increase of sympathetic activity, whereas it may delay the repolarization process, suggesting that inhibition of potassium-channel trafficking might be induced more acutely In vivo than those previously expected in vitro. Keywords:: pentamidine, monophasic action potential, QT prolongation, torsades de pointes, trafficking